Newborns are sensitive to the correspondence between auditory pitch and visuospatial elevation - Walker, Peter *; Bremner, James Gavin; Lunghi, Marco; Dolscheid, Sarah; Dalla Barba, Beatrice; Simion, Francesca (Wiley, 2018)
Amodal (redundant) and arbitrary cross-sensory feature associations involve the context-insensitive mapping of absolute feature values across sensory domains. Cross-sensory associations of a different kind, known as correspondences, involve the context-sensitive mapping of relative feature values. Are such correspondences in place at birth (like amodal associations), or are they learned from subsequently experiencing relevant feature co-occurrences in the world (like arbitrary associations)? To decide between these two possibilities, human newborns (median age = 44 hrs) watched animations in which two balls alternately rose and fell together in space. The pitch of an accompanying sound rose and fell either congruently with this visual change (pitch rising and falling as the balls moved up and down), or incongruently (pitch rising and falling as the balls moved down and up). Newborns' looking behaviour was sensitive to this congruence, providing the strongest indication to date that cross-sensory correspondences can be in place at birth.